Fabrication effects on polysilicon-based microcantilever piezoresistivity for biological sensing application - Nina Korlina Madzhi,; Anuar Ahmad,; Balkish Natra,; Mastura Sidek,; Lee, Yoot Khuan (Universiti Kebangsaan Malaysia, 2011)
In principle, adsorption of biological molecules on a functionalized surface of a microfabricated cantilever will cause a surface stress and consequently the cantilever bending. In this work, four different type of polysilicon-based piezoresistive microcantilever sensors were designed to increase the sensitivity of the microcantilevers sensor because the forces involved is very small. The design and optimization was performed by using finite element analysis to maximize the relative resistance changes of the piezoresistors as a function of the cantilever vertical displacements. The resistivity of the piezoresistivity microcantilevers was analyzed before and after dicing process. The maximum resistance changes were systematically investigated by varying the piezoresistor length. The results show that although the thickness of piezoresistor was the same at 0.5 μm the resistance value was varied.